A model for curriculum development in nursing - Louise de Villiers (AOSIS, 2001)
A curriculum model for curriculum development in nursing and the health sciences is discussed. Opsomming 'n Model vir kurrikulumontwikkeling in Verpleegkunde en die gesondheidswetenskappe word bespreek. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.